Invited panel member of the Global Family Business Think Tank 2024, Family Business United - Hadjielias, Elias (My University, 2026)
Global Family Business Think Tank of, Family Business United https://www.familybusinessunited.com/post/family-business-united-launches-second-global-think-tank-findings
Keywords: Business and industry